A rare case report on Chiari malformation and syringomyelia-related Charcot arthropathy - Paneyala , Shasthara; Naaz, Soofia; Chirravuri, Pallavita; Thejesh, C V (Indian Journal of Case Reports, 2025)
Charcot arthropathy is a progressive and often underrecognized joint condition typically resulting from impaired sensory innervation. Although commonly associated with diabetes, it may also occur in the context of less frequent neurological disorders. This report discusses the case of a 27-year-old woman who presented with chronic swelling and restricted movement of the right elbow, without a history of trauma or systemic symptoms. Imaging studies eventually revealed syringomyelia and Chiari malformation as the underlying causes. This case underscores the need for clinicians to consider neuropathic arthropathy in the differential diagnosis of unexplained joint dysfunction, particularly in the upper limbs, and to use advanced imaging techniques like magnetic resonance imaging for timely identification and intervention before irreversible joint damage occurs.